Faktor-faktor yang mempeng aruhi persepsi remaja usia 14-15 tahun tentang narkoba - Menuf Ayu UmborowatI, Sumarni P., Nawi Ng (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Drug abuse among young adolescents has become more prevalent in Indonesia recently. Youth psychological development and their perception on drug use are among factors associated with drug abuse. Youth perception on drug abuse has not yet been studied in-depth in Indonesia. Therefore, this study was conducted to explore the young adolescent's perception on drug abuse and its determinant in Indonesia. Method: Eight Focus Group Discussion (FGD) was conducted among the 91h grade students in Yogyakarta City and Purworejo District. Three in-depth interviews with junior high school teachers were done to triangulate the results from student. Result: The youth in this study has negative perception on drugs. The boys knew the harm and bad consequences of using drug. They were aware that drug abuse is forbidden by religion and it is a sin to do so, and this was stressed upon particularly by urban youth. Drug abuser got punishment from school and this become another motivation for not using drug. The youth agreed that exposure to alcohol will promote youth's acquaintance to drugs. Conclusion: Young adolescent's perception on drugs is affected by their psychological developmental stage, their value and understanding of religion, their knowledge about drugs, and their exposure to peers, families, neighborhood, and school. These factors worked differently between rural and urban youth. Keywords : drugs abuse, youth, perception, qualitative method, urban and rural